Keefektifan Layanan Bimbingan Kelompok dengan Media Film dalam Meningkatkan Self Esteem - Sauqi, Kamaludin Reza (Indonesian Journal of Guidance and Counseling: Theory and Application, 2017)
The purpose from this research is to see the effectiveness of group guidance service within increase child self esteem at Yayasan Setara, Semarang. This type of research is experimental research with pre experimental design with a kind of one group pre test and post test design. Subject of this research is 5 grade student of PL Servatius Elementary School. Collecting data technique in this research using a psychological scale and collecting data tool using likert scale with 42 number of declaration point that has been tested before. Data analysis methods is using with wilcoxon test. Research has done to see self esteem before group guidance with film media given show that self esteem criteria in middle level (67,91%). Child self esteem after group guidance with film media given counted to high criteria (80,43%). Self esteem increased 12,52% after group guidance with film media given. Highest increase occurred in self improvement indicator with 16% percentage. Lowest increase indicator with 10,67% is self adjustment indicator. Wilcoxon test result tcount= 55 and ttable= 8, tcount> ttable, so Ho rejected and Ha accepted.